Assessing Spatial Distribution And Accessibility Of Public Primary Schools In Mafraq City, Jordan: A Gis-Based Approach - A. A. AlFanatseh (Geography, Environment, Sustainability)
The spatial accessibility of educational services is important in planning and managing educational services. This study seeks to evaluate the spatial distribution of basic schools, find the optimal location for the distribution of those schools, and develop solutions and proposals to improve accessibility by creating new schools. p-median models were applied to allocate sites. After analysing the locations of schools and demand points (residential buildings) in the city of Mafraq, where this model tries to provide recommendations regarding the area that service should cover, the standards of the Ministry of Education were adopted; they stipulate that the distance between the site of the basic school and the residential building should range 750 m. Accordingly, two models were applied: The first scenario was applied to evaluate the current school sites, whereas the second suggested the establishment of new schools in underserved areas and the evaluation of the effectiveness of accessibility after the construction of new schools. The results of the study showed that the number of unserviced demand points according to the optimal criterion for distance of access is approximately 58.9%, while it decreased to 38% after proposing the establishment of 10 schools in new locations. The study concluded that the analysis of site allocation using p-median models is an effective method in the spatial planning of schools. It can assist decisionmakers and urban planners in improving accessibility to primary schools by establishing new schools and upgrading access to existing schools in underserviced areas..